HALAL-LOGISTICS VALUE CHAIN ON FIRM PERFORMANCES: A CONCEPTUAL FRAMEWORK - Hasrul Hashom; Ahmad Shabudin Ariffin; Rohafiz Sabar; Hartini Ahmad (International Journal on Food, Agriculture and Natural Resources, 2020)
Various research on logistics has been conducted to examine Logistics Service Provider (LSP) firm performances in many angles. This is important since logistics service has become an important industry globally and the trend also absorb in Malaysia`s commercial market. Growing in innovation trend was also effected logistics when demand on green logistics take place in international stages on awareness over environmental issues. In line with this development, halal-value creation concept also emerges and constructively contribute to the sustainability of the industry. Therefore, there is a discrepancy in the study of business models, particularly on the firm performance that have not yet been tested in the role of halal and green logistics as a catalyst for marketing strategies that can benefit a company. Thus, this concept paper will conduct an effort and check previous literature related to business performance to see the direct relationship on halal and green logistics as independent variable toward firm`s performance. Through this conceptual study, halal-green logistics will be dedicating as element of sustainability marketing in firm`s performance; which environmental and contamination issues will be highlights and address accordingly. This study will propose Resource-based View Theory as underpinning theory to prove inclination of relationship between variables. Finally, the paper will provide Halal-Logistics Value Chain conceptual framework as initiative to facilitate the global community of researchers and practitioners in understanding the diversity, meaning, and evolution of the halal-green logistics phenomenon in the context of emerging economies, also as improving firm performance.